1981
DOI: 10.1002/pssa.2210660228
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties and non-stoichiometry in ZnO single crystals

Abstract: The electrical conductivity and the Hall effect are investigated in the temperature region fiom 77 to loo0 K on undoped ZnO single crystals grown by vapour phase transport. The growth conditions were systematically altered to get crystals with definite non-stoichiometry. The electrical properties are related to these growth conditions. The analysis of the Hall data yields the phase boundary ZnO/Zn and a formation enthalpy of 1.5eV for the dominant native donor. This donor is suggested to be the oxygen vacancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(92 citation statements)
references
References 34 publications
2
89
0
1
Order By: Relevance
“…10 The decrease in the band gap from 3.35 to 3.25 eV can be explained by the Burstein-Moss effect. 11 An air annealing of degenerate AZO films removes surplus electrons occupying the energy states above the bottom of the conduction band, thereby decreasing both the optical band gap and electron concentration.…”
Section: Resultsmentioning
confidence: 99%
“…10 The decrease in the band gap from 3.35 to 3.25 eV can be explained by the Burstein-Moss effect. 11 An air annealing of degenerate AZO films removes surplus electrons occupying the energy states above the bottom of the conduction band, thereby decreasing both the optical band gap and electron concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Transmittance of the films was more than 80 % in the visible region regardless of O 2 :Ar composition and substrate temperature. In the direct transition semiconductor, the optical absorption coefficient (α) and optical energy band gap (E g ) are related by [10] …”
Section: Optical Properties and Resistivitymentioning
confidence: 99%
“…If the ionization energies of these defects are low, the system will tend to be an intrinsic n-type conductor. Some early studies have indicated that vacancies are shallow donors in these oxides [29][30][31][32][33][34][35][36][37][38], but more recent analysis based on plane-wave density functional theory (DFT), first using a Hubbard U parameter then, in later studies, a hybrid functional, tends to place them as deep centers in many TCOs [20,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Of those that have been shown to form shallow centers [41,[56][57][58][59], it has been argued that their compact wave functions preclude the possibility of them contributing to n-type conductivity [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic n-type conducting properties of ZnO are well established [36,37,[76][77][78][79], with carrier concentrations in undoped samples up to 5 × 10 19 cm −3 (in thin films) [80]. Some experiments [81,82] have shown a variation in conductivity and mobility with P O 2 more indicative of the presence of interstitials or cation vacancies (which have also been shown to be present using positron annihilation spectroscopy) [83][84][85][86][87], but oxygen vacancies have been proposed to explain the intrinsic n-type conductivity [36,78,88] and persistent photoconductivity [37,76], as well as other experimental results [89][90][91][92].…”
Section: Introductionmentioning
confidence: 99%